New Light on and Scientific Analysis of a Late Neo- Elamite Copper Alloy Fitting Reportedly from Tang-i Sarvak in the Bakhtiyari Highlands of Southwest Iran - J. Simpson, St; Mongiatti, A.R. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
A late Neo-Elamite bronze fitting in the form of a seated female figure acquired at Tang-i Sarvak and in the British Museum can now be dated between the mid-7th and mid-6th centuries BC through analogy with excavated finds from the site of Jubaji. These also confirm its function as a decorative fitting on a shallow copper alloy scoop, contradicting earlier suggestions that it had been a furniture fitting attributed to an earlier period. This paper reviews these changes, provides the first scientific analysis of the object which indicates how it was made, and what the metal composition is, and concludes with a brief exploration of the wider significance of the find.